Evola's interpretation of fascism and moral responsibility. (19th October 2016) - Wolff, Elisabetta Cassina
ABSTRACT: The ideological influence that several right-wing radical thinkers exercised on the Norwegian 'lone wolf' terrorist Anders Behring Breivik raises the question of how far a writer can be held responsible for acts of terrorism s/he may have influenced. Italian history provides a vital lesson in this respect: namely, the role played by the Italian traditionalist Julius Evola in the crucial passage from Fascism to neo-fascism. After reviewing Evola's ideological development, Wolff then analyses Evola's influence on a young generation of neo-fascists in Italy. Another relevant topic is the ideological continuity between Fascism and neo-fascism identified here, as centred on Evola's view of 'general fascism' as the Traditional right.